Agreement Between Self-Reported Information and Administrative Data on Comorbidities, Imaging and Treatment in Denmark - A Validation Study of 38,745 Patients with Knee or Hip Osteoarthritis - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2021)
Purpose: To validate self-reported information obtained from patients with knee or hip osteoarthritis (OA) in primary care against administrative data from the three national Danish registries. Patients and Methods: We compared the baseline and 12-month follow-up data from 38,745 patients with knee or hip OA participating in the Good Life with osteoArthritis in Denmark (GLA:D (R)) program with registry-based data on joint surgeries, pain medication dispensing, radiographs, and hospital diagnoses. Agreement was calculated using Cohen's Kappa (k) and percentage agreement, both with 95% CI. Results: There was a moderate agreement between self-report and registry-based data for previous knee surgery (k=0.58, 84.99%) and a substantial agreement for previous hip surgery (k=0.73, 97.05%). Agreement varied from 0.05 to 0.95 and 84.99% to 99.94% for different types of surgeries with lowest agreement for collateral ligament surgery (k=0.05, 99.82%) and highest agreement for joint replacement (k=0.95, 99.54% for knee; k=0.95, 99.48% for hip). There was a moderate agreement (k=0.41, 81.59%) for knee and a slight agreement (k=0.20, 64.79%) for hip radiographs. Agreement varied from 0.01 to 0.53 and 65.39% to 99.90% for pain medication with lowest agreement for topical NSAID (k=0.01, 95.00%) and highest agreement for opioids (k=0.53, 92.56%). For comorbidities, agreement varied from 0.14 to 0.90 and 78.07% to 98.91%, with lowest agreement for anemia or other blood disease (k=0.14, 97.63%) and highest agreement for diabetes (k=0.90, 98.73%). Conclusion: As the most common types of pain medication used by patients with OA can be bought over-the-counter and as most OA patients are treated in primary care, which is often not covered by national registries, self-report of pain medication use and comorbidities is preferred but cannot be sufficiently validated against registry-based data. Future studies collecting self-reported information on joint surgery and pain medication from patients with OA should use a less detailed categorization to improve accuracy.
Keywords: self-report; data validity; osteoarthritis; Denmark; POSITIVE PREDICTIVE-VALUE; HEALTH-CARE UTILIZATION; CLINICAL VALIDATION; QUESTIONNAIRE DATA; CHRONIC DISEASES; MEDICAL RECORDS; PROCEDURE CODES; DIAGNOSES; ACCURACY; REGISTRY